Coaching Clinic Penulisan Artikel Ilmiah dan Proposal Hibah untuk Peningkatan Produktivitas Akademik - Muhammad Zalviwan; Aris Setiawan; Muchammad Ariffin; Siswadi; Ida Ayu Suci; Akbar Fadly Pratomo (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2026)
This community service activity took the form of a Coaching Clinic on Scientific Article Writing and Higher Education Research Proposals, organized by the Research and Community Service Institute (LPPM) of Panca Bhakti University (UPB). The core issues addressed were the still-low rate of scientific publications by faculty members and the lack of competitiveness in grant proposals, which directly impact the institution’s Key Performance Indicators (KPIs). The activity aims to strengthen faculty members’ capacity to produce publication-ready scientific articles, select reputable journals, and draft competitive grant proposals. The method used was an interactive coaching clinic featuring two expert speakers from Wijaya Kusuma University in Surabaya and Tanjungpura University: Dr. Lusy Tunik Muharlisiani, M.Pd, and Prof. Dr. Ir. Yohana S.K. Dewi, MP. The participants were faculty members from UPB Pontianak. The results of the activity showed a significant improvement in participants’ understanding of research proposal writing, structured articles, appropriate journal selection, and avoiding predatory journals. The activity also strengthened academic collaboration between institutions and received a highly positive response from participants.